A pilot study on salivary cortisol secretion and auditory P300 event-related potential in patients with physical disability-related stress - Vorasith Siripornpanich (2020)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. Objective: To evaluate the stress level and attention in workers with physical disabilities-related stress. Methods: Morning salivary cortisol was used as a stress marker while the event-related potential during the performance of the auditory oddball paradigm was conducted to investigate the attentive ability to sound stimuli. Eighteen injured workers (IP) and eighteen unaffected healthy adults (CP) were recruited for this study with half being men and the other half women (aged 21–55). Behavioral performance measures including reaction time (RT), accuracy rate, and commission error as well as the latency and amplitude of P300 wave over the central (Cz), centroparietal (CPz), and parietal (Pz) electroencephalogram electrode sites were used to compare the two groups. Results: This study demonstrated significantly higher salivary cortisol levels, longer RT, less accuracy to respond to the target during the auditory oddball paradigm in the IP group as compared to CP group. In addition, a significant prolongation of the peak latency of auditory P300 wave over CPz electrodes was also detected in IP group. Conclusion: The increased cortisol levels found in the IP group reflect the alteration of the basal hypothalamic-pituitary-adrenal axis as a result of the stresses of living with a physical disability. Delayed RT and the decreased in accuracy together with changing in peak latencies of auditory P300 wave indicate the impairment of attention networks in IP. Our study revealed that the patients with permanent physical disability.